ANALYSIS OF SARA'S POST-CONFLICT MULTICULTURAL EDUCATION: INDIGENOUS PSYCHOLOGICAL STUDIES - Hasanuddin Hasanuddin; Fikriyah Iftinan Fauzi; Muhammad Abrar Parinduri (State Islamic University (UIN) Ar-Raniry, 2023)
The purpose of this study is to analyze the extent to which multicultural education can stand alone as an independent entity in educational institutions in Tanjung Balai City after the SARA-nuanced conflict. The results of interviews with teachers and students of SMAN 1 Tanjung Balai revealed that this school tries to integrate multicultural values in the curriculum. However, multicultural education has not been separated as an independent entity. Teachers design the curriculum by emphasizing cultural and religious diversity in learning materials. Students confirm that the concept of diversity is reflected in school learning and activities. This study used a data analysis approach based on the Miles and Huberman framework. The results show that multicultural education in Tanjung Balai focuses on integrating cultural values in learning, but still needs more efforts to realize independent multicultural subjects. Multicultural education has the potential to bridge cultural and religious differences, but it needs professional teacher involvement and appropriate strategies to support the development of religious tolerance among students.